Production of ornamental pyramid pepper with reflective material on benches in different environments - Silva, Laura Araujo; Salles, Josiane Souza [UNESP]; Cambui Neto, Luiz Martins; Costa, Edilson; Silva, Abimael Gomes [UNESP]; Cavalcante, Daniele Ferreira; Silva Binotti, Flavio Ferreira da; Zoz, Tiago (Univ Estadual Mato Grosso Sul, 2021)
Pepper trees have great ornamental value due to the varied colors of their fruits. Thus, the objective was to evaluate the Pyramid cultivar's production in different cultivation environments using benches with reflective material. The experiment was carried out in two protected environments: a) agricultural greenhouse with 42-50% shade screen under the plastic film and b) agricultural screen with black monofilament screen with 18% shade. Inside the environments, the production system was tested with and without reflective material on the cultivation bench. The experiments were conducted in a completely randomized design, with four replicates and six plants per plot. Joint analysis was used to compare environments. At 45, 60, and 75 days after transplantation, plant height, stem diameter, number of leaves, canopy area, and number of fruits were evaluated. The agricultural greenhouse with a 42/50% shade screen under the plastic film provided the formation of higher plants with greater stem diameter, greater number of leaves and fruits, and greater top diameter than the screen with 18% shading. The reflective mirror material showed positive results only for plant height.
Keywords: Capsicum frutescens; Pyramid cultivar; Mirror